Exact Lexicographic Scheduling For Sales Force Optimization With Facility Constraints. - Prakash, A.; Balakrishna, U. (Journal of Neonatal Surgery, 2025)
There are I=1,2,3,…..,n be set of n persons, J=1,2,3,…..,m be set of m schedules and k=1,2,3,……,p be set of p facilities. S (t, j) is the number of calls made in jth schedule at time t. SB (t) is the minimum number of calls to be made by the persons at time t. C (i, j, k) is the cost of assigning jth schedule to ith person at facility k i.e., the cost depends on the facility k which is the third independent factor which influences the cost. The restriction is: If the same schedule is assigned to different persons then the facilities should be different. The problem is to assign the schedules to n1 (<n) persons with minimum cost with the above restriction and the total number of calls made in each time is greater than SB(t). In the sequel we will develop a Lexi Search algorithm based on the ‘Pattern Recognition Technique’ to solve this problem which takes care of the simple combinatorial structure of the problem.